Antiparasitic drugs in children. - White, N (1989)
Many of the children living in tropical areas of the world are infected by a variety of human parasites. As a group, the antiparasitic drugs can claim to be the least studied of all compounds in current clinical use. There is little information on the disposition of these drugs in children, and most treatment recommendations are either empirical or by extrapolation from observations in adults. Many of the older drugs used in systemic parasitic infections have narrow therapeutic ratios and could be better used if treatment regimens were based on detailed pharmacokinetic and pharmacodynamic information. This review summarises existing information on these drugs and suggests provisional recommendations for antiparasitic treatment.